Kinship and belonging: Pacific children's perspectives on the diaspora. (November 2022) - Freeman, Claire; Latai Niusulu, Anita; Schaaf, Michelle; Taua'a, Tuiloma Susana; Tanielu, Helen; Ergler, Christina; Kivalu, MaryJane
Our study with 71 children aged 6-14 living in New Zealand and Samoa, provides a new child-centred perspective on transnational diasporic families. We use the Pacific concept vā to frame the study, in which children's transnational-kinship connections reflect relational rather than physical approaches to space. Familial habitus surpasses spatial habitus as children's primary reference point. For diasporic children, family keeps alive their sense of Pacific Island belonging. Transnational kinship ties give Pacific children additional resilience in adapting to unknown futures.